Growth Rate of Usnea aurantiacoatra (Jacq.) Bory on Fildes Peninsula, Antarctica and Its Climatic Background - Li, Ying; Kromer, Bernd; Schukraft, Gerd; Bubenzer, Olaf; Huang, Man-Rong; Wang, Ze-Min; Bian, Lin-Gen; Li, Cheng-Sen (PLoS ONE, 2014)
The ages of a fruticose lichen of Usnea aurantiacoatra (Jacq.) Bory, from Fildes Peninsula, King George Island, Southwest Antarctic, were determined by radiocarbon (C-14), and it is 1993-1996 at bottom and 2006-2007 at top of the lichen branch. The growth rates of U. aurantiacoatra calculated are 4.3 to 5.5 mm year(-1) based on its length and ages. The comparisons show that the growth rates of U. aurantiacoatra are higher than those of U. antarctica (0.4 to 1.1 mm year(-1)). The growth rates of fruticose lichens are always higher, usually > 2 mm year(-1), than those of crustose ones, usually < 1 mm year(-1), in polar areas. A warming trend on Fildes Peninsula is recorded in the period from 1969 to 2010 obviously: the mean annual temperature rose from -2.75 to -1.9 degrees C and the average temperature of summer months from 0.95 to 1.4 degrees C, as well as the average temperature of winter months from -6.75 to -5.5 degrees C. The alteration of lichen growth rates in polar areas may respond to the climatic and environmental changes, and the lichens may act as bio-monitor of natural condition.